2011
DOI: 10.1016/j.livsci.2011.07.015
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a prebiotic supplement (Prebio Support) on fecal and salivary IgA in neonatal dairy calves

Abstract: The newborn calf's gastrointestinal tract is sterile at birth, but by 3 days of age coliforms, Lactobacilli, and Bifidobacteria are the predominant flora in the feces. During the preweaning period, calves are susceptible to diarrhea that can lead to high levels of morbidity and mortality. Diarrhea has been related with a decrease of beneficial microbiota and an increase of coliform counts in feces. Prebiotic supplements are believed to decrease diarrhea and positively affect some parameters of the immune syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…Ghosh and Mehla () observed decreased faecal coliform count in MOS fed group. In the line of present study, lactobacilli count in faeces was higher ( p < .05) and Bifidobacteria tended to be higher ( p < .07) in calves fed prebiotic (Quezada‐Mendoza, Heinrichs, & Jones, ).…”
Section: Discussionsupporting
confidence: 61%
“…Ghosh and Mehla () observed decreased faecal coliform count in MOS fed group. In the line of present study, lactobacilli count in faeces was higher ( p < .05) and Bifidobacteria tended to be higher ( p < .07) in calves fed prebiotic (Quezada‐Mendoza, Heinrichs, & Jones, ).…”
Section: Discussionsupporting
confidence: 61%
“…; Quezada‐Mendoza et al . ), and cellooligosaccharides (CE), which are derived from enzymatic digestion of plant cellulose, may be a good supplement for stocker calves. An in vitro study revealed that cellobiose (a disaccharide consisting of glucose with a beta‐1‐4 linkage) caused generation of organic acids by mixed ruminal bacteria (Lila et al .…”
Section: Introductionmentioning
confidence: 99%
“…Al‐Saiady () observed greater serum IgG concentration and greater 5‐week BW in calves supplemented with a probiotic. However, there were no impacts on serum IgG concentrations in calves provided with a prebiotic supplement (Queszada‐Mendoza et al., ). In both these studies, calves were over 24 hr old and AEA was not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…() found no impact of DFM on plasma IgA, IgG and IgM concentrations in dairy goats, but immunoglobulin in the mammary secretions was not evaluated. Queszada‐Mendoza, Heinrichs, and Jones () found no effect of probiotics on plasma, faecal or salivary IgG concentrations in calves. These differing outcomes suggest that there is potential for DFM to increase IgG content in dairy cattle colostrum, which could impact the health of the calf through more IgG available for absorption, as well as impact the health and production of the cow when fed post‐partum.…”
Section: Introductionmentioning
confidence: 99%